Waste Management Awareness Education for Elementary School Teachers and Students; the Implementation of Sustainable Environmental Education - Darussyamsu, Rahmawati; Helendra, Helendra; Arsih, Fitri; Ristiono, Ristiono; Fajrina, Suci; Ramayani, Mia; Riski, Shintia Putri (Pelita Eksakta, 2024)
In fact, awareness of waste management is still low in Nagari Tanjung Balik, Solok Regency. Based on initial observations, it is known that students at Nagari Tanjung Balik Elementary School do not yet have awareness of waste management. Furthermore, even though since 2022, Nagari Tanjung Balik has had a Waste Bank under the guidance of Universitas Negeri Padang Community Development Team, there has been no contribution from the total of five elementary schools in Nagari Tanjung Balik to the Waste Bank. This is of course not in line with the Nagari Tanjung Balik program which has attempted to intensify waste management in order to create a sustainable environment. Therefore, the solution offered is to provide education to elementary school students who are members of the KKG Cluster III Tanjung Balik Elementary School, X Koto Above District regarding waste management.